METODE IJTIHAD DALAM KONSTRUKSI HUKUM TAHKIM INDONESIA - Nurul Khikmah; Karimatul Khasanah (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2022)
Tahkim or arbitration is a form of resolving disputes out of court. Peace efforts such as in tahkim or arbitration aimed at reconciling the warring parties have existed and have long been practiced in the customs and culture of the Indonesian nation. Alongwith the increasing need for an arbitration peace model to resolve conflicts amid the rapid development of sharia business in Indonesia today, formulating a sharia tahkim model that accommodates local values needs to be considered. rules of fiqh clearlystate that al-hukmuyadurruma’aillatihi wujudan waadaman, that the law is enforced according to ilat whether it exists or does not exist, as well as the taghayyural-ahkam bitaghayural amkinat waal-azman rule that the law changes according to changes in place and time. The type of this research is juridical philosophical with maslahahapproach. The data sources used are secondary and consist of three legal materials: primary, secondary, and tertiary. The type of this research is juridical philosophical with maslahah approach. The data sources used are secondary data sources consisting of three legal materials, namely primary, secondary and tertiary. The analysis was carried out using a descriptive inductive technique. The results of this study are that several ijtihad methods such as istihsan, maslahah mursalah, and especially the technique of establishing law with 'urf can be used to realize Indonesian Tahkim fiqh. The selection of these three methods, especially the 'urf which is based on benefit and istihsan is very suitable for conditions in Indonesia, considering that a culture of peace rooted in adat is still very strong.